Changes in Corneal Volume at Different Areas and Its Correlation with Corneal Biomechanics after SMILE and FS-LASIK Surgery. (27th April 2020) - Wei, Pinghui; Cheng, George PM; Zhang, Jiamei; Ng, Alex LK; Chan, Tommy CY; Jhanji, Vishal; Wang, Yan
Abstract : Purpose . To investigate the variations of corneal volume (CV) after small incision lenticule extraction (SMILE) and femtosecond laser-assisted laser in situ keratomileusis (FS-LASIK) and analyze the influences of biomechanical properties on the changes of refraction and CV. Methods . Ninety-seven eyes of 97 patients undergoing SMILE and FS-LASIK were included in this retrospective study. CV was measured with Scheimpflug-based corneal topography at preoperatively and at day 1, week 1, and months 1 and 3 postoperatively. CV measured within 5 mm diameter was defined as central region volume (CV5) and between 5 mm and 10 mm diameter was defined as peripheral region volume (CV5-10). An Ocular Response Analyzer (ORA) was used to assess corneal biomechanical properties including corneal hysteresis (CH) and corneal resistant factor (CRF). The reduction of study parameters (△) were calculated by subtracting the preoperative value at various time points from the postoperative values. Results . CV had significant reduction after the SMILE and FS-LASIK procedure (P < 0.05 ). CV5 increased significantly from postoperative day 1 to month 3 (P < 0.001 ) in SMILE, while both CV5 and CV5-10 increased significantly in FS-LASIK (P < 0.001 ). The increase in CV5 after SMILE was 0.11 ± 0.16 mm 3 ，which was significantly different from FS-LASIK (0.20 ± 0.13 mm 3, P = 0.004 ). In the SMILE group, △CV5 correlated with △CRF ( r  = 0.498, P < 0.001 ) and △CH ( r  = 0.374, P = 0.007 ). In the FS-LASIK group, △CV5 and △CRF had a significant correlation ( r  = 0.363, P = 0.012 ), but not with △CH. Conclusions . Dynamic changes in corneal volume were found after SMILE and FS-LASIK surgery. The central region significantly increased after SMILE, while both central and peripheral regions increased following FS-LASIK in the early postoperative period. SMILE was associated with less change in biomechanical properties per unit of reduction in CV compared with FS-LASIK.